2021
DOI: 10.5435/jaaos-d-20-01301
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Management of Posterior Wall Acetabulum Fractures

Abstract: Posterior wall acetabulum fractures typically result from high-energy mechanisms and can be associated with various orthopaedic and nonorthopaedic injuries. They range from isolated simple patterns to multifragmentary with or without marginal impaction. Determination of hip stability, which can depend on fragment location, size, and displacement, directs management. Although important in the assessment of posterior wall fractures, CT is unreliable when used to determine stability. The dynamic fluoroscopic exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
0
15
0
1
Order By: Relevance
“…The KL approach was obviously performed for the PWs in PC+PW, T+PW, and TV+PW. Furthermore, the intra-articular fragments and marginal impaction must be identified carefully and stabilized appropriately because these are the known factors affecting clinical outcomes [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KL approach was obviously performed for the PWs in PC+PW, T+PW, and TV+PW. Furthermore, the intra-articular fragments and marginal impaction must be identified carefully and stabilized appropriately because these are the known factors affecting clinical outcomes [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fractures of the posterior wall (PW) are the most common types of the acetabulum [ 1 , 2 ]. It has been reported that the PW fractures may be isolated or associated with other acetabular injuries, including posterior column, T shape, transverse, and both-column fractures [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main indication for fixation of the PW fragment is hip instability 1,4,25 . The anterior displacement tendency of the PW and femoral head were eliminated for the block of fixed main fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive fracture comminution makes it difficult to achieve anatomical reduction and is more likely to lead to poor clinical results [ 13 ]. We excluded PWFs without radiographic anatomical reduction and focused on the significance of the area where the fracture was comminuted.…”
Section: Discussionmentioning
confidence: 99%